Analisis Perbaikan Downtime Mesin Injection Molding dengan Pendekatan DMAIC di PT XYZ - Mohamad Faris Rahmadsyah; Moch. Tutuk Safirin (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Machine downtime is a daily issue in the manufacturing industry. Handling downtime occurrences on machines is necessary to improve productivity and the quality of production outcomes. This becomes a benchmark for manufacturing companies to compete in the era of globalization. The DMAIC approach can be utilized to systematically analyze and resolve issues, including downtime problems. Research findings indicate that hot runner mold is a priority for improvement at PT XYZ. Through the Define, Measure, and Analyze stages of DMAIC, the main problems are clearly identified, their causes deeply analyzed, and effective solutions developed and tested. The implementation of these solutions through the Improve and Control stages successfully enhanced production efficiency, reduced downtime, and improved mold quality.